The Effect of Laying Nozzle Distance Position on Operational Results Renewable Power Plant Pico-Hydro - Eswanto; bin Mohamad Razlan, Zuradzman; Lida, Akiyoshi (International Journal of Integrated Engineering, 2023)
New and renewable energy sources today and in the future are human needs that need to be sought and explored from all existing nature, especially in countries with many sources of application, such as Indonesia. Indonesia is an archipelago country that has a vast nature with abundant alternative energy sources such as river flow, irrigation which can be used as a source of energy for pico-hydro power plant. The purpose of this study was to determine the performance of pico-hydro with a test model for the position of nozzle position mounted on the pico-hydro using screw Archimedes turbine. The research method is carried out by direct experimentation from a tool that has been made using water fluid that is circulated continuously as if in actual operating conditions. The results of this research show that the positioning of the nozzle distance as the water output to drive the turbine blades affect operational results obtained. The farther distance from nozzle position to thread, the power and rotation also decrease, on the other hand, if nozzle is too close, the water sprayed by nozzle causes a back force of water so that the results are not optimal. In this research, the greatest power is generated at a nozzle distance of 4 cm, which is 230 Watt at a flow rate of 24 m3/h, and the lowest power is obtained at 44 Watt at flow rate of 2 m3/h where this position is ideal for pico-hydro installation. The best turbine shaft rotation in this study was produced at a nozzle distance of 4 cm which is 195 rpm, in this condition the spray of water flowing out of the tip of the nozzle towards the screw blade of the first part of the turbine which hits the sidelines of the screw occurs without resistance.